IMPLEMENTASI PERJANJIAN SEWA MENYEWA TANAH OLEH PT. KAI KEPADA PT. HERONA EXPRESS PEKALONGAN : ANALISIS AKAD IJARAH - Dewi Hasna Layaliya; Heris Suhendar; Satria Budiman (el hisbah: Journal of Islamic Economic Law, 2022)
Economic transactions are carried out by humans in completing their needs. One of them is a lease such as a land lease agreement made by PT. KAI with PT. Herona Express Pekalongan. However, PT. KAI amended the agreement in which the tenant is asked to leave the leased land on the grounds that it will be used as PT.KAI's operations. Even though the lease period has not expired and the tenant has not violated the terms of the agreement. Then the tenant is given land in a new location to be rebuilt with a new agreement. This research is a library research with a qualitative approach. The results of this study indicate the implementation of land leases by PT. KAI to PT.Herona Express that the land lease agreement began in 2010. Then in 2014 it was extended on Tuesday, July 8, 2014 in Bandung with an Asset Lease Agreement of PT. KAI (Perrsero) No.Hk..221/VII/1/KA-2014. Regarding the object of the lease of PT. Herona Express Pekalongan has an area of ​​15 m2 at a cost of Rp. 46.020,000 lease period 4 years 11 months starting 01 June 2014 - 30 April 2019. Analysis of the ijarah agreement on the implementation of land lease by PT. KAI to PT. Herona Express Pekalongan in terms of the pillars, terms, and procedures for terminating the ijarah contract are in accordance with the syara'. In its implementation, there is a change in the agreement that is allowed because it prioritizes public needs with the construction of a food court, the convenience of tenants, and the provision of compensation in the form of relocation. Therefore, if analyzed specifically with the ijarah contract, the actions taken by PT. KAI to PT. Herona Express Pekalongan is allowed in the ijarah agreement.